Daar : kunst in de openbare ruimte Enschede 1990-2000. - Baan Müller, Pieter; Derriks, Saskia; Hoet, Jan; Könings, Hans; Musterd, Lucie; Möring, Marcel; Swart, Marco P.; Weijsters, Arend-Jan; van Eldik, Ellen (Enschede : Dienst Maatschappelijke Ontwikkeling van de gemeente Enschede, 2001)
Benus, Anna Thalia ; Bosch, Karin ; Devens, Paul ; Dings, Nicolas ; Gudmundsson, Sigurdur ; Hovy, Hans ; Kwerreveld, Wilco ; van der Leeden, Gerard ; Neddam, Martine ; Oortwijn, Kees ; Sales, Sjef ; Sterren, Gé-Karel Van Der ; van der Vossen, Anne-Karien ; Wandemaker, Jeroen ; Willemsen, Cees ; Zacharias, Simone
boek